Pelaksanaan Discharge Planning Pada Pasien Hipertensi Di Puskesmas Latalola Besar - Yerry Soumokil; Franseska Aulele; La Ode Irsan (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2023)
Hypertension is a non-communicable disease that is still a problem in the field of health. Hypertension treatment efforts have basically been executed in various ways including activities to increase knowledge of hypertensive patients. Knowledge can be improved through education information communication. One of the most commonly performed health workers on health services is the implementation of discharge planing. discharge planning is planning to go home, from hospital admission until the patient is discharged by a health worker. Research Method: This research is a descriptive research with retrospective approach. The population in this study is the medical records of hypertensive patients who received hospitalization and was declared to return from july to agust 2023. The amount of research sample counted 145 medical record of hypertension patient by using slovin formula. The sample size of each ward uses the fraction cluster sampling formula. The research instrument uses a health education checklist.The results show that the overall health education program 145 (100%) was conducted, mostly using the 145 (100%) discussion method, the patient's or family's response to hypertension after being given a health education largely understood but unable to explain itself 113 ( 77.93%), most health education providers were implemented by doctors 135 (93.10%), and most health education recipients were received by families of hypertensive patients 122 (84.14%).